Upgradation of biomass-derived furfural by nanostructured layered double hydroxides: Influence of stirring rate on structural features of materials - Bhagat, Shailesh K.; Nagpure, Atul S.; Lanjewar, Mamata R.; Gode, Nilesh G.; Deshmukh, Ganpat D.; Saini, Ajay (Inorganic Chemistry Communications, 2025)
The proficient conversion of biomass-derived compounds into the high-quality platform chemicals and bio-fuels is enormously imperative to decrease dependence on fossil feedstock. Furfural is a significant bio-based chemical which can be efficiently converted to valuable 4-(2-furyl)-3-buten-2-one (FAc) via aldol condensation. In this work, we have developed prominent layered double hydroxides (LDHs) catalysts for mild aldol condensation of furfural and acetone to acquired high performance with admirable FAc selectivity. Various nanostructured Mg-Al LDHs were synthesized through co-precipitation procedure under different stirring rate conditions. The structural, morphological and optical attributes of materials as well as recyclability aspect and structure-activity relationship was examined by characterizing the fresh and spent catalysts via numerous techniques (XRD, N2 sorption, DLS, CO2-TPD, NH3-TPD, FT-IR, UV-Visible spectroscopy, TGA, SEM, TEM, ICP-OES, 27Al NMR spectroscopy, XPS, Raman spectroscopy, etc). Several reaction parameters were also optimized. Among the catalysts tested, LDH-1200 catalyst exhibits outstanding performance by delivering 100% furfural conversion with 99% FAc selectivity. Moreover, catalyst illustrates excellent recyclability and stability. The mechanistic insight for aldol condensation was also investigated by monitoring the intermediates at different stages and intervals during the course of the reaction. This study confirms that stirring rate has significant influence on physico-chemical attributes of materials and the amount of weak basic sites plays imperative role in catalytic performance.
Keywords: Aldol condensation; Biomass-derived compounds; Flower-shaped nanocrystals; heterogeneous catalysis; Nanostructured mesoporous LDH